Genetic alterations in human papillomavirus-associated oropharyngeal squamous cell carcinoma of patients with treatment failure. (June 2019) - Reder, Henrike; Wagner, Steffen; Gamerdinger, Ulrike; Sandmann, Sarah; Wuerdemann, Nora; Braeuninger, Andreas; Dugas, Martin; Gattenloehner, Stefan; Klussmann, Jens Peter; Wittekindt, Claus
Highlights: Genetic alterations are common in OPSCC primaries from patients with recurrence. Notably higher mutation frequencies were found in HRAS, TP63, PIK3R1 and STK11 . TP53 mutations are detectable in patients with HPV-associated OPSCC and recurrence. tNGS panel sequencing might complement for patient selection regarding treatment. Abstract: Objectives: Despite improved survival rates of patients with HPV-associated OPSCC, a subset has distant metastasis or develops local recurrence during follow-up. To investigate potential underlying genetic alterations, we analyzed patients with HPV-driven OPSCC who suffered from recurrence in comparison to matching pairs with successful tumor control. Materials and methods: We performed chromosomal copy number analyses and targeted next generation sequencing using a custom panel comprising genes that are frequently mutated in HPV-associated OPSCC. Results: Specific differences regarding chromosomal aberrations were not observed between both groups. In HPV-driven OPSCC from patients with recurrence we found higher mutation rates compared to patients with successful tumor control. Especially mutation rates of HRAS (p ≤ 0.05) PIK3R1, STK11 and TP63 (p ≤ 0.1 each) were statistically significant or trending towards significance. The respective genes can be linked to transcription factors and signaling pathways involved in cell cycle regulation, proliferation and survival. Additionally, combinations of alterations were observed on chromosomes 16 and 19, which might also influence outcome. Conclusion: Patients with HPV-driven OPSCC who develop recurrence or have metastasis may be defined by genetic alterations that might be responsible for poor outcome after standard therapy. This might be of importance for stratification in future de-escalation and targeted therapy.